أثر التَّعَلُّم التَّنْظيميِّ فِي تَعزِيز الابْتكار التِّكْنولوجيِّ دِراسة تطْبيقيَّة على كُلِّيَّات عُنيْزَة فِي الممْلكة العربيَّة السُّعوديَّة: The Impact of Organizational Learning on Enhancing Technological Innovation An Applied Study on Onaizah Colleges in the Kingdom of Saudi Arabia - محمود كمال عربي; رضوي رضوان محمد (Journal of North African Economies, 2025)
The study aimed to analyze the impact of organizational learning in its various dimensions on enhancing technological innovation atOnaizah College in the Kingdom of Saudi Arabia, using a sample of 105 faculty members and staff. The study adopted a descriptive-analytical approach and utilized a questionnaire to collect data, which were analyzed using SPSS software, incorporating statistical methods such as arithmetic means, standard deviations, correlation coefficients, and simple and multiple regression analyses. The results showed a positive and statistically significant relationship between organizational learning and technological innovation, with organizational learning explaining 64% of the variance in technological innovation, and supportive leadership for learning being one of the most influential dimensions. The study recommended adopting strategies that encourage knowledge exchange and collaboration among employees, enhancing industry-university partnerships, and providing an organizational environment that fosters dialogue and inquiry and develops effective information systems, to achieve a shared collective vision that supports innovation and continuous development, in support of Saudi Arabia’s Vision 2030.